Controllable MnCo2S4 nanostructures for high performance hybrid supercapacitors. Issue 16 (5th April 2017) - Elshahawy, Abdelnaby M.; Li, Xin; Zhang, Hong; Hu, Yating; Ho, Kuan Hung; Guan, Cao; Wang, John
Abstract : Sulphospinel materials, such as MnCo2 S4, are being widely investigated as a promising class of candidates for energy storage. Abstract : Sulphospinel materials, such as MnCo2 S4, are being widely investigated as a promising class of candidates for energy storage. The low electric conductivity and low surface area derived by the conventional processes have however limited their wide usage as a class of low-cost materials for energy storage. In this work, sulphospinel MnCo2 S4 nanostructures have been rationally synthesised through a carefully controlled sulphurization process, which expresses a desirable mesoporous feature with high electrical conductivity. They show much better electrical conductivity and pronounced improvement in the electrochemical performance with a high capacitance (938 F g −1 at 20 A g −1 ) and excellent cycling stability, where the specific capacitance could be retained at 95% of its original value after 5000 charge–discharge cycles. To further demonstrate the great potential of sulphospinel materials, a full-type supercapacitor was assembled with MnCo2 S4 on carbon cloth as the positive electrode and a (Porous Carbon Polyhedron) PCP/rGO hydrogel as the negative electrode. The full cell shows a high energy density of 43 W h kg −1 at a power density of 0.801 kW kg −1, and 16.2 W h kg −1 can be retained at a power density of 26.5 kW kg −1 . Excellent cycling stability is also achieved with 87% retention after 10 000 charge–discharge cycles, demonstrating great potential for next-generation high performance supercapacitors.